Semi-Skilled Labour and Food Security in Nigeria in the Fourth-Republic: An Assessment of FCT Abuja, Nigeria - Ayeni , Felix; Ibori, Musa Salihu (Kashere Journal of Politics and International Relations, 2023)
The paper examined Rice production and Food Security in Nigeria’s fourth republic between 2007 and 2015 as well as identifying the contribution of artisans towards the uplift of the rural economy in the Federal Capital Territory (FCT), Abuja. Production theory was adopted for this study. The data for the study were lifted from primary sources and these were supplemented by secondary data. The findings of this study revealed that the services of road-side mechanics and plumbers as artisans assist to boost rice farming through their involvement in the area of tractor repair and irrigational equipment repair respectively; which are meant to augment the skilled labour of the engineers. However, the findings also revealed that over the years, FCT-ADP has shown less desire regards to encouraging artisans; has failed to provide credit facilities such as loans to them; and besides, FCT-ADP has failed to train them in modern technical skills which have indirectly led to fewer improvement in rice production output in the FCT. The paper concluded that the lack of government intervention policy on the acquisition of technical skills outside the school system has to some extent affected the growth of Rice-Food Security in the FCT. Therefore, the paper recommended that FCT-ADP should motivate the artisans by granting them the opportunity to get recruited into public and private farms as well as granting them the requisite training to be abreast with modern challenges in the agricultural sector, step up rural economic growth, thereby curbing the rate of poverty in the rural areas of the FCT.